2011
DOI: 10.4297/najms.2011.3137
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic and multiple plasmodium falciparum infections in pregnant Sudanese women

Abstract: Background:Control of malaria during pregnancy remains a major public health challenge in developing countries. Microscopic parasite detection represents a pivotal step in malaria control, while modern molecular techniques are deemed to improve detection rates markedly.Aims:This study aimed to investigate the frequency of submicroscopic and multiple Plasmodium falciparum (P. falciparum) infections during pregnancy, using the P. falciparum merozoite surface protein1 (MSP-1) gene as a polymorphic marker.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
2
7
1
Order By: Relevance
“…With successive pregnancies, women acquire a gravidity-dependent anti-malarial immunity, resulting in a decrease in both prevalence and severity of infection (Smith et al, 1999). Studies have demonstrated a correlation between the MOI and parasite density as well as age of the study participants (Mayengue et al, 2004;Omer et al, 2011). In our study, MOI was associated with neither maternal age nor gravidity, which is in line with other study (Kassberger et al, 2002, Walker-Abbey et al, 2005.…”
Section: Discussionsupporting
confidence: 90%
“…With successive pregnancies, women acquire a gravidity-dependent anti-malarial immunity, resulting in a decrease in both prevalence and severity of infection (Smith et al, 1999). Studies have demonstrated a correlation between the MOI and parasite density as well as age of the study participants (Mayengue et al, 2004;Omer et al, 2011). In our study, MOI was associated with neither maternal age nor gravidity, which is in line with other study (Kassberger et al, 2002, Walker-Abbey et al, 2005.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, these variants may not be detected in placental smears [ 30 ]. On the other hand, submicroscopic malaria infections are common during pregnancy and more sensitive approaches like placental histology are needed to detect sub-microscopic infections [ 31 ].. A certain level of host immunity may also contribute to microscopically undetectable densities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise comparison revealed that pregnant women had higher mean number of clones than children and adults. This is an indication that they carry a greater diversity of parasites, possibly reflecting infection with both placenta-specific and non-specific parasites, especially in primigravids [ 41 43 ]. Interestingly, the number of clones was observed to increase in individuals carrying gametocytes as compared to those who did not carry gametocytes.…”
Section: Discussionmentioning
confidence: 99%